Peptide Receptor Radionuclide Therapy with 177 Lu-DOTA-TATE As a Promising Treatment of Malignant Insulinoma: a Series of Case Reports and Literature Review - Magalhães, D (2019)
Introduction: Insulinomas are a rare type of pancreatic neuroendocrine tumours characterized by insulin hypersecretion. They are considered malignant when metastases are present. Traditional therapies often promote only temporarily symptomatic relief and may be associated with severe adverse effects. There is scarce experience in treating malignant insulinomas with peptide receptors radionuclide therapy (PRRNT). Patients and methods: We describe PRRNT results in four patients with inoperable malignant insulinomas with poorly controllable hypoglycaemia. All patients received therapy with 177Lu-DOTA-TATE after conventional therapies failed in controlling disease progression and symptoms. The activity administered per cycle was 4.8-7.4 GBq. The interval between cycles was 10-16 weeks. Haematology, liver and kidney function tests were performed before treatment initiation and 5 and 10 weeks after each cycle. Results: Patient 1 presented significant clinical benefit for 13 months after PRRNT, with imaging improvement. Patient 2 obtained reduction of the number and severity of hypoglycaemic episodes during 15 months after therapy. Patient 3 is asymptomatic since PRRNT first cycle performed 23 months ago and revealed significant imaging improvement. Patient 4 had resolution of hypoglycaemia only 3 days after PRRNT first cycle and today, 16 months after therapy, the disease seems to be in remission and the patient maintains euglycaemic state. PRRNT was well tolerated, with only hematologic grade 2 toxicity in patient 1 and mild kidney toxicity in patient 3. Conclusions: After the start of 177Lu-DOTA-TATE all patients achieved hypoglycaemia symptomatic control and had evident improvement of their quality of life. Three patients showed imagiological improvement suggesting reduced tumour load.